Immunomodulatory therapy, risk factors and outcomes of hospital-acquired bloodstream infection in patients with severe COVID-19 pneumonia: a Spanish case–control matched multicentre study (BACTCOVID). (November 2021) - Abelenda-Alonso, Gabriela; Rombauts, Alexander; Gudiol, Carlota; Oriol, Isabel; Simonetti, Antonella; Coloma, Ana; Rodríguez-Molinero, Alejandro; Izquierdo, Elisenda; Díaz-Brito, Vicens; Sanmartí, Montserrat; Padullés, Ariadna; Grau, Inmaculada; et al.
Abstract: Objectives: The effect of the use of immunomodulatory drugs on the risk of developing hospital-acquired bloodstream infection (BSI) in patients with COVID-19 has not been specifically assessed. We aim to identify risk factors for, and outcomes of, BSI among hospitalized patients with severe COVID-19 pneumonia. Methods: We performed a severity matched case–control study (1:1 ratio) nested in a large multicentre prospective cohort of hospitalized adults with COVID-19. Cases with BSI were identified from the cohort database. Controls were matched for age, sex and acute respiratory distress syndrome. A Cox proportional hazard ratio model was performed. Results: Of 2005 patients, 100 (4.98%) presented 142 episodes of BSI, mainly caused by coagulase-negative staphylococci, Enterococcus faecalis and Pseudomonas aeruginosa . Polymicrobial infection accounted for 23 episodes. The median time from admission to the first episode of BSI was 15 days (IQR 9–20), and the most frequent source was catheter-related infection. The characteristics of patients with and without BSI were similar, including the use of tocilizumab, corticosteroids, and combinations. In the multivariate analysis, the use of these immunomodulatory drugs was not associated with an increased risk of BSI. A Cox proportional hazard ratio (HR) model showed that after adjusting for the time factor, BSI was associated with a higher in-hospital mortality risk (HR 2.59; 1.65–4.07; p < 0.001). Discussion: Hospital-acquired BSI in patients with severe COVID-19 pneumonia was uncommon and the use of immunomodulatory drugs was not associated with its development. When adjusting for the time factor, BSI was associated with a higher mortality risk. Graphical abstract: Image 1